Excessive exercise training causes mitochondrial functional impairment and decreases glucose tolerance in healthy volunteers - Flockhart, Mikael; Nilsson, Lina C; Tais, Senna; Ekblom, Björn; Apró, William; Larsen, Filip J (Cell metabolism, 2021)
Exercise training positively affects metabolic health through increased mitochondrial oxidative capacity and improved glucose regulation and is the first line of treatment in several metabolic diseases. However, the upper limit of the amount of exercise associated with beneficial therapeutic effects has not been clearly identified. Here, we used a training model with a progressively increasing exercise load during an intervention over 4 weeks. We closely followed changes in glucose tolerance, mitochondrial function and dynamics, physical exercise capacity, and whole-body metabolism. Following the week with the highest exercise load, we found a striking reduction in intrinsic mitochondrial function that coincided with a disturbance in glucose tolerance and insulin secretion. We also assessed continuous blood glucose profiles in world-class endurance athletes and found that they had impaired glucose control compared with a matched control group.